THE INFLUENCE OF HUMAN RESOURCES QUALITY, BUDGET PLANNING AND ORGANIZATIONAL COMMITMENT ON BUDGET ABSORPTION WITH THE USE OF INFORMATION TECHNOLOGY AS A MODERATING VARIABLE IN LOCAL EQUIPMENT ORGANIZATIONS IN KARIMUN DISTRICT - Supriyono; Bambang Satriawan; Irfan; Muammar Khaddafi (RADJA PUBLIKA, 2022)
In the era of regional autonomy, an interesting phenomenon has occurred, namely the minimal absorption of the Regional Revenue and Expenditure Budget in most parts of Indonesia, both at the provincial, district and city levels. The lack of absorption of the budget arises amid demands for more transparent and accountable management and accountability of state and regional finances in the framework of good governance and demands for effectiveness and efficiency. This phenomenon also occurs in the Karimun Regency Government where there are delays in budget absorption in quarter I to quarter III which in turn results in low realization or absorption of the budget at the end of the year, therefore the authors are interested in conducting research on the author's thesis entitled Effects of Human Resource Quality . , Budget Planning and Organizational Commitment to Budget Absorption by Using Information Technology as a Moderation Variable in Regional Apparatus Organizations in Karimun Regency.